Early detection of risks in child development in Spanish-speaking countries: content validity - Llanos, Luis Felipe; Martínez de Anguita, María (Frontiers in Pediatrics, 2025)
IntroductionEarly detection of developmental disorders like ADHD, ASD, and LD is critical for improving educational outcomes and enabling timely interventions. This study aimed to develop a reliable, practical screening scale for Spanish-speaking children entering primary education, addressing gaps in early identification within the region.MethodsIn total, 151 items were identified. With a qualitative methodology and with the help of 18 specialists in child therapy from various Spanish-speaking countries, stabilized content validity. The analysis was articulated in its aspects of relevance.ResultsThe validation process identified 18 items with strong psychometric properties. These items demonstrated high levels of agreement among experts and strong content validity, forming the foundation for a culturally relevant screening tool. The scale is designed to identify developmental risks early and support timely interventions in educational and clinical settings.DiscussionThe study underscores the importance of efficient screening tools for primary education, especially in regions with limited access to early childhood education. Future research will validate the scale in larger, diverse samples to ensure its reliability, establish cutoff points, and confirm its generalizability across Spanish-speaking contexts.